Características de las páginas web en español que brindan información sobre aborto - Alvarado-Zeballos, Samira (2017)
Abstract Introduction: Women who decide to have an abortion look for related information using different means, including web pages which could have erroneous or poor quality data. Objectives: To describe the characteristics of web pages in Spanish that provide information on abortion and assess the quality of those that include advice on self-induced abortion. Materials and methods: A systematic Google search of Spanish websites that provide information on abortion was carried out and the frequency of pages with an incorrect statement was measured. To evaluate associated factors, Poisson regressions were performed, calculating prevalence ratios (PR) and 95% confidence intervals (95% CI). The quality of the sites that provide recommendations on self-induced abortion was evaluated using the Curró criteria. Results: 73 web pages were obtained, of which 38 presented some incorrect statement, being blogs the most frequent source (PR=1.58, CI95%: 1.03-2.41). The most frequent areas in which incorrect statements were found were “abortive methods that do not work” and “instructions for performing an abortion.” Out of the 19 web pages that presented recommendations on self-induced abortion, only 1 had complete adherence to therapeutic guidelines, while 16 had no references and 18 had commercial sponsorship. Conclusions: A considerable amount of web pages in Spanish that provide information on abortion have incorrect statements and do not adhere to therapeutic guidelines. This can promote risky health behaviors in women who seek information on the topic.